ผู้นำสตรีกับการจัดการความขัดแย้งในชุมชนแถบลุ่มน้ำโขงตอนล่าง - จรัญศิรไพศาล สายกุหลาบ (Journal of Human and Society, Sisaket Rajabhat University, 2022)
การวิจัยครั้งนี้ ผู้วิจัยมีวัตถุประสงค์เพื่อศึกษาผู้นำสตรีกับการลดความขัดแย้งในชุมชนแถบลุ่มน้ำโขง เพื่อวิเคราะห์เกี่ยวกับสิทธิสตรีในการเป็นผู้นำชุมชนสตรีมีส่วนร่วมลดความขัดแย้งในชุมชนอย่างไรบ้างในแถบลุ่มลำน้ำโขงตอนล่าง โดยใช้กระบวนการวิจัยเชิงคุณภาพจากผู้นำสตรีในองค์กรทั้งภาครัฐและเอกชนราชอาณาจักรไทยในพื้นที่จังหวัดสุรินทร์ ราชอาณาจักรกัมพูชาในพื้นที่จังหวัดเสียมเรียบ และสาธารณรัฐประชาธิปไตยประชาชนลาวในจังหวัดจำปาสัก ผลการศึกษาครั้งนี้ทำให้ทราบการได้มาถึงสิทธิสตรีในการเป็นผู้นำชุมชนแล้วนำไปสู่ในการลดความขัดแย้งในชุมชน สร้างให้ชุมชนมีความสงบสุขสร้างสันติสุขในสังคมอย่างยั่งยืนในอนุภูมิภาค ลุ่มน้ำโขง ศึกษาคุณลักษณะสตรีที่เป็นผู้นำชุมชนในชุมชนภาคตะวันออกเฉียงใต้ตอนล่าง ค้นหาแนวทางและข้อเสนอแนะเชิงนโยบายเกี่ยวกับสตรีเพื่อลดความขัดแย้งในชุมชนสร้างสันติสุขในสังคมโดยรวม The purpose of this study was to study women leaders and conflict reduction in the communities of the Lower Mekong Basin to analyze the rights of women as leaders of communities and how they participated in conflict reduction in the community of the Lower Mekong Basin. The researcher used quality research process from women leaders in both government and private organizations in Surin Province, the Kingdom of Thailand; Siam Reap Province, the Kingdom of Cambodia; and Champasak Province, the Lao People’s Democratic Republic. The result of this study revealed how to acquire women’s rights in community leadership which led to conflict reduction in communities in order to create a sustainable peace in the area of Mekong Basin. Also, it was to study characteristics of women who were community leaders in the lower southeastern communities to find guidelines and policy recommendations on women to reduce conflict in the community and to create peace in society as a whole.